Long-term mortality in HIV patients virally suppressed for more than three years with incomplete CD4 recovery: A cohort study - Engsig, Frederik N; Gerstoft, Jan; Kronborg, Gitte; Larsen, Carsten S; Pedersen, Gitte; Røge, Birgit; Jensen, Janne; Nielsen, Lars N; Obel, Niels (BMC infectious diseases, 2010)
Background The mortality in patients with persistent low CD4 count despite several years of HAART with sustained viral suppression is poorly documented. We aimed to identify predictors for inadequate CD4 cell recovery and estimate mortality in patients with low CD4 count but otherwise successful HAART. Method In a nationwide cohort of HIV patients we identified all individuals who started HAART before 1 January 2005 with CD4 cell count ≤ 200 cells/μL and experienced three years with sustained viral suppression. Patients were categorized according to CD4 cell count after the three years suppressed period (≤ 200 cells/μL; immunological non-responders (INRs), >200 cells/μL; immunological responders (IRs)). We used logistic regression and Kaplan-Meier analysis to estimated risk factors and mortality for INRs compared to IRs. Results We identified 55 INRs and 236 IRs. In adjusted analysis age > 40 years and > one year from first CD4 cell count ≤ 200 cells/μL to start of the virologically suppressed period were associated with increased risk of INR. INRs had substantially higher mortality compared to IRs. The excess mortality was mainly seen in the INR group with > one year of immunological suppression prior to viral suppression and injection drug users (IDUs). Conclusion Age and prolonged periods of immune deficiency prior to successful HAART are risk factors for incomplete CD4 cell recovery. INRs have substantially increased long-term mortality mainly associated with prolonged immunological suppression prior to viral suppression and IDU.